2005
DOI: 10.1002/adsc.200404247
|View full text |Cite
|
Sign up to set email alerts
|

Metallodendritic Catalysis for Redox and CarbonCarbon Bond Formation Reactions: A Step towards Green Chemistry.

Abstract: Metallodendritic catalysts combine the advantages of homogeneous and heterogeneous catalysts: they are soluble and perfectly well defined on the molecular level, and yet they can be recovered by precipitation, ultra-filtration or ultra-centrifugation (as biomolecules) and recycled several times. In this article, we summarize our recent work in this field with examples operating under ambient conditions in metathesis, Pd-catalyzed Sonogashira coupling, redox catalysis of nitrate and nitrite cathodic reduction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 76 publications
(33 reference statements)
0
42
0
Order By: Relevance
“…This strategy was also applied to related fully polyoxometalate (POM)-centered dendrimers. [119][120][121][122] Functionalizaton of olefin-terminated dendrimers by hydrosilylation reactions using chlorosilanes has been achieved in particular in van Leeuwen's divergent dendrimer synthesis 123 and using chloromethyldimethylsilane by Seyferth, both with 1/2 connectivity. 58 Chlorodimethylsilane could also be used for a direct one-pot iterative dendrimer synthesis with 1/3-connectivity up to G3-243-allyl.…”
Section: Functionalizations Of the Dendrimers For Applicationsmentioning
confidence: 99%
“…This strategy was also applied to related fully polyoxometalate (POM)-centered dendrimers. [119][120][121][122] Functionalizaton of olefin-terminated dendrimers by hydrosilylation reactions using chlorosilanes has been achieved in particular in van Leeuwen's divergent dendrimer synthesis 123 and using chloromethyldimethylsilane by Seyferth, both with 1/2 connectivity. 58 Chlorodimethylsilane could also be used for a direct one-pot iterative dendrimer synthesis with 1/3-connectivity up to G3-243-allyl.…”
Section: Functionalizations Of the Dendrimers For Applicationsmentioning
confidence: 99%
“…The reaction between benzaldehyde, aniline and cyclohexanone as a model reaction in water in the presence of various amounts of first generation dendrimer [6][7][8][9][10][11][12][13][14]. It was found that only 2 mol % of the catalyst was required to drive the reaction smoothly to completion.…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of use, there is still much interest in developing new approaches for C C bond coupling, and recent attention has focussed on a range of areas including the development of new catalysts [4], design of water based organometallics [5] and the use of metallic nanoparticles [6]. One of the most widely studied classes of C C bond coupling reactions are metal mediated reductive coupling of organohalides, the so called "Wurtz" reaction [7].…”
Section: Introductionmentioning
confidence: 99%